Ahl as Sunnah waal Jama - Anwar, Khairil (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2022)
This study focused on the early history of the emergence of the ahl as-sunnah waal-jamāʻah (Sunnism) and its development in Indonesia. This study also compared al-Banjari's Sunnism with Indonesia's Islamic group Nahdlatul Ulama